DOI: 10.29007/3nl1
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve and Alignment Assessment of an Image-Free Handheld Robot in TKA: The First Patient Series in Europe

Abstract: BACKGROUND: The typical goal of TKA is to obtain a neutral mechanical axis of the leg. The NAVIO® Surgical System (Smith & Nephew, Pittsburgh, PA, USA) is aimed at reducing technical errors and outliers. The aim of this study is to assess the surgeons’ learning curve and limb alignment in TKA.METHODS:The first sixty-nine patients who underwent TKA with the NAVIO system by two experienced surgeons were included in this study. Pre- and postoperative mechanical limb alignment and balancing was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Many authors demonstrated that after an initial learning curve with a long operation time, surgeons could expect a significant reduction in operative time after a small number of cases with this system [43, 46,47]. In particular, the average surgical time for a surgeon approaching NAVIO ® TKAs was reported as 68.2 min, compared to an average of 51.7 min for cTKA [43].…”
Section: Outcomes and Cost-effectivenessmentioning
confidence: 99%
“…Many authors demonstrated that after an initial learning curve with a long operation time, surgeons could expect a significant reduction in operative time after a small number of cases with this system [43, 46,47]. In particular, the average surgical time for a surgeon approaching NAVIO ® TKAs was reported as 68.2 min, compared to an average of 51.7 min for cTKA [43].…”
Section: Outcomes and Cost-effectivenessmentioning
confidence: 99%